A Guidebook for Assessing Mathematical Logic Intelligence in Kindergarten - Indah Abdiana; Nenny Mahyuddin (Journal of Education Reseach and Evaluation, 2024)
Many children still need help understanding numbers; children also cannot differentiate between round, triangular, and square shapes. Apart from that, teachers only carry out assessments at the end of the learning semester and do not use assessment guides, especially on aspects of children's mathematical logic intelligence in their daily activities at school. Based on this, this research aims to develop a guidebook for assessing mathematical logic intelligence in kindergarten. This type of research is development research. This research uses the ADDIE model. The research subjects are learning media experts and learning material experts. The test subjects were fifteen teachers. The methods used to collect data are interviews, documentation, and questionnaires. The data collection instrument uses a questionnaire sheet. The data analysis technique used is quantitative descriptive statistical analysis. The research results are the results of material media validation tests with a test percentage value of 96.3% and the eligibility criteria being "very valid." The assessment from media experts was 98.7%, with the eligibility criteria being "very valid." The assessment score from the effectiveness instrument expert has a test percentage value of 97%, with the eligibility criteria being "very valid." The effectiveness test of individual trials were 95.69% "very effective" and small group 91.67% "very effective". It was concluded that the mathematical logic intelligence assessment guidebook is very suitable and adequate for teachers in kindergarten. The research implication is that the developed mathematical logic intelligence assessment guidebook can be used in learning activities.